Changes in colour and location as cues of generative transmission in perception of causality. Issue 4 (21st April 2018) - Hubbard, Timothy L.; Ruppel, Susan E.
ABSTRACT: Observers viewed modified launching effect displays containing a spatial gap between the final location of the launcher (a black square) and the initial location of the target (a black outline square with a white interior). In some conditions, a set of stationary objects (black outline squares with white interiors) filled the spatial gap, and these objects began changing colour upon contact from the launcher. The colour changes could involve all gap objects turning black, the first gap object turning dark grey and subsequent gap objects turning successively lighter grey, or first gap object turning light grey and subsequent gap objects turning successively darker grey. The colour changes could move from the launcher to the target or from the target to the launcher. The gap objects could also remain unchanged. Participants rated whether the launcher caused subsequent motion of the target and how much force the launcher imparted to the target. The sequence of colour changes, and the sequence of locations in which colour changes occurred, influenced ratings; sequences of colour changes consistent with the idea that influence of the launcher was transmitted across gap objects to the target resulted in higher ratings. Implications for visual perception of causality are discussed.